PRES or ODS: An atypical presentation of osmotic demyelination syndrome? - Joshua Wiley, DO; Mark Colantonio, MD; Nisha Hollingsworth, MD; Jonathan Shakesprere, MD (Radiology Case Reports)
Osmotic demyelination syndrome is a rare, but life-threatening condition requiring prompt identification and treatment. Classically, this pathology is associated with overcorrection of hyponatremia. Few cases have explored alternative etiologies, including large variation in blood glucose as well as beer potomania. Here, we present a case of osmotic demyelination syndrome secondary to derangements of blood glucose in the setting of eunatremia.